2017
DOI: 10.18203/2320-1770.ijrcog20171436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maternal and neonatal outcome in elective lower segment cesarean section done at 38 and 39 weeks

Abstract: Background: Time to perform elective LSCS is a relevant issue related to mother and foetus. LSCS can be done from 37 weeks onwards because foetal lungs mature by then. But foetuses born at 37 weeks of gestation have more risk of developing respiratory problems, transient tachypnoea of new born, hypothermia, hypoglycaemia and NICU admission.The purpose of this study is to find out appropriate gestational age at which elective LSCS can be performed without adverse maternal and neonatal outcome.Methods: This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The present study revealed that the incidences of complications like PPH and bladder injury were comparable when ECS was done at early term or full term. It was observed that LUS was not adequately formed when ECS was done at 38 weeks as compared to 39 weeks (p=0.0071) in an observational study by Gisi et al 12 RCT done by Glavind et al demonstrated that the composite maternal outcomes in the form of blood loss, bladder bowel injury, uterine rupture or dehiscence, procedural difficulty, uterine incision tear were not statistically significant (p=0.63) when ECS was performed at 38 weeks in comparison to 39 weeks. 13 For all the enrolled patients under the present study, no maternal death, ICU admission, thromboembolic event were observed because of the low risk of developing intra-operative and post-operative complications, due to proper booking, supervision and uncomplicated pregnancy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The present study revealed that the incidences of complications like PPH and bladder injury were comparable when ECS was done at early term or full term. It was observed that LUS was not adequately formed when ECS was done at 38 weeks as compared to 39 weeks (p=0.0071) in an observational study by Gisi et al 12 RCT done by Glavind et al demonstrated that the composite maternal outcomes in the form of blood loss, bladder bowel injury, uterine rupture or dehiscence, procedural difficulty, uterine incision tear were not statistically significant (p=0.63) when ECS was performed at 38 weeks in comparison to 39 weeks. 13 For all the enrolled patients under the present study, no maternal death, ICU admission, thromboembolic event were observed because of the low risk of developing intra-operative and post-operative complications, due to proper booking, supervision and uncomplicated pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…An observational comparative research conducted by Gisi et al and RCT conducted by Glavind et al compared neonatal outcomes when ECS was performed at 38-38 6/7 versus 39-39 6/7 and 38 +3 versus 39 +3 weeks, respectively and observed that the incidence of NRM was not statistically significant when ECS was done at 38 weeks or 39 weeks. 12,13 On the contrary, Shraddha et al in their retrospective study done in India noticed that the incidence of NRM was 15.8% and 6.3% in neonates, delivered at ET and full-term (FT) respectively (p=0.007). 14 Another observational retrospective study performed by Sujata et al in Indian setup found that the incidence of NRM was 17.6% at 37 weeks, 5.6% at 38 weeks, 5.1% at 39 and 2.8% beyond 40 weeks.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although there was no significant difference in Apgar score, respiratory distress, NICU admission was seen when both groups were compared. 25 Parikh et al study found that early term births (37 0/7-38 6/7 weeks) accounted for 34.1% of term births. NICU admission and respiratory distress were lowest at or beyond 39 weeks compared to the early term period for most precursors, while indicated deliveries had the highest morbidity compared to other precursors.…”
Section: Discussionmentioning
confidence: 97%